Primary lung cancer with duodenal metastasis complicated by obstructive jaundice and pancreatitis: a case report - Kuang, Jie; Chen, Yanan; Xie, Huikang; Hao, Hua; Zhao, Yanlin; Tang, Cui (Frontiers in Oncology, 2025)
BackgroundPrimary lung adenocarcinoma with duodenal metastasis is relatively rare, and its early clinical symptoms are often insidious, making diagnosis challenging. CT, MR, PET-CT, and gastroscopy can effectively identify gastrointestinal metastatic lesions, providing reliable evidence for definitive diagnosis and treatment planning, which contributes to prolonging patient survival.Case presentationThis report presents a rare case of duodenal metastasis from lung adenocarcinoma. The patient was diagnosed with lung adenocarcinoma (cT4N3M1c, stage IVb) one year prior. During chemotherapy, the patient gradually developed symptoms of abdominal distension and progressive jaundice. Through analysis of CT and MR imaging changes during the disease course, combined with laboratory test indicators, malignant duodenal tumor causing biliary obstruction and pancreatitis was suspected. Ultimately, endoscopic pathological biopsy confirmed duodenal metastasis from primary lung cancer. The clinical surgeon implemented a PTCD treatment plan, successfully relieving the patient’s biliary obstruction.ConclusionsPrimary lung cancer patients presenting with abdominal symptoms and imaging findings suggestive of gastrointestinal tumors should be highly suspected of metastasis. Timely pathological diagnosis is essential to determine the nature and origin of the tumor, thereby facilitating the formulation of individualized treatment plans.